Incidence of Pelvic and Paraaortic Lymph Node Metastasis in Epithelial Ovarian Cancer at a Tertiary Care Center - Andrijono Andrijono; Risa Risfiandi (Indonesian Society of Obstetrics and Gynecology, 2018)
Objective: To investigate the incidence of pelvic and paraaortic lymph node metastasis in epithelial ovarian cancer. Methods: This was a cross-sectional study. Data were collected from medical records, and from the cancer registry 1539 medical records were obtained. From there, 863 patients were operated and 676 were not, and only 401 medical records were found complete, and 306 samples were excluded because they have been treated with NAC and underwent surgery, patients who underwent surgery but the results is not the epithelium, and patients who underwent surgery, but the results were benign or borderline. And 95 patients who underwent primary surgery and lymphadenectomy only 55 patients have results in lymphadenectomy. This study uses a calculation of sample size with categorial descriptions, with precision of 3% then obtained a minimum sample size of 261 patients. Results: According to the characteristics of the study subjects above, the results were stage I, II, III respectively 60%, 10.9%, and 29%. The metastasized of the lymph node paraaortic 9.1%, and pelvic/paraaortic 20% pelvic/paraaortic23.6%. Based on the degree of differentiation the results were good differentiation 30.9%, moderate differentiation 23.6%, and poor differentiation 45.5%. We found that paraaortic lymph node metastasis were most frequent at stadium III (43.8%). In relationship between lymph node metastasis with differentiation of epithelial ovarian cancer, the most frequent epithelial ovarian cancer were one with poor differentiation in pelvic/paraaortic lymph node with the sum of 69.2%. From analysis, there is significant difference between serous hystologic subtype with mucinosum subtype in pelvic lymph node, significant difference between serous hystologic subtype and clear cell in paraorta or pelvic lymph node and between the serous histology subtype and mucinous as well. Conclusion: Lymph node metastasis incident of ovarian epithelial cancer in paraaorta amounts 20%, pelvic 9.1% and pelvic or paraaortic 23.6%. Higher the stadium, the lymph node involvements will be higher as well (pelvic and paraaortic). In stadium 1 of mucinous subtype with well differentiation has minimal lymph node involvement so we can be more selective in considering the risk and benefit of lymphadenectomy. [Indones J Obstet Gynecol 2018; 6-1: 60-63] Keywords: lymph node metastasis, ovarian cancer